TAFSIR SAYYIDINA AHMAD KHAN - Muhammad Adji Saputra; Dani Abdul Latif; Indah Namiratuz Zahra; Putri Hudani Nabila; Andi Rosa (Adisam Publisher, 2025)
Tafsir of Sayyid Ahmad Khan represents a significant intellectual contribution to Islamic thought, emphasizing a rational and contextual approach in understanding the Qur’an. This study aims to analyze how Khan interprets Qur’anic verses by taking into account social, historical, and contemporary scientific contexts, making his exegesis relevant and applicable to modern society. The research employs a qualitative descriptive method based on library research, collecting data through the review of literature, books, journal articles, and credible online sources. The analysis reveals three main aspects in Khan’s tafsir: (1) rationality in interpreting divine revelation to align with logic and scientific knowledge, (2) the use of tafsir as a tool for intellectual renewal and apologetics to address external criticism and social challenges, and (3) contextualization to ensure that Qur’anic verses can be applied in modern life without compromising moral and legal values of Islam. Therefore, Khan’s tafsir not only explains the text literally but also provides moral, social, and political guidance that remains relevant, making it a model of integration between revelation and human reason. This study recommends utilizing Khan’s tafsir as a reference for academics, Islamic education practitioners, and the wider Muslim community to understand the Qur’an rationally, critically, and contextually.